Case ReportCutaneous-subcutaneous pseudolymphoma after specific immunotherapy with grass-rye pollen-allergen extract containing aluminium hydroxide - Kreft, Burkhard; Bednarczyk, Magdalena; Emmerling, Franziska; Marsch, Wolfgang Christian (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Allergen-specific immunotherapy is an important treatment procedure in IgE-mediated allergic diseases such as allergic rhinitis or insect toxin allergies. A reduction in the clinical reaction to the allergens to which the patient is known to be sensitized is intended by means of antigen-specific influence on the immune system. The allergen-specific immunotherapy can be applied by subcutaneous injections, and for selected allergens by means of sublingual application of the appropriate allergen. Occasionally, the injection of aluminium hydroxide-adsorbed sera induces a usually transient formation of granulomas. We are reporting on a rare case of cutaneous-subcutaneous pseudolymphoma in the injection area of both upper arms, probably induced by subcutaneous allergen-specific immunotherapy.